Real-time Image Processing in Embedded Vision Systems for Autonomous Vehicles - Venugopal, Vedanarayanan; Mohanty, Monalisa; Boregowda, Vinay Kumar Sadolalu; Singh, Suraj; Singh, Manpreet; Deepthi, Pochampalli; Deepak, Shashikant (International Journal of Engineering, Science and Information Technology, 2025)
The most recent studies show that the benefits of the IT improvements associated to ads were substantial. These days, there is a lot of controversy over the optimal way to store, retrieve, and access personal and other data.Since systems are developing so quickly and clients may now access information virtually from anywhere, delivering personal or official information on a physical device has become outdated. This is how distributed computing has emerged and expanded to meet the needs of efficiency, security, unwavering quality, and laziness. The widespread use of Internet of Things devices promises to alter some aspects of our lifestyle. The delivery of human services services is being transformed by other individual Internet of Things devices, such as wearable wellness, wellness monitoring devices, and system-powered restorative devices. This invention promises to benefit the elderly and others with disabilities, enabling higher degrees of independence and personal fulfilment at an affordable price. According to the legally enforceable claim, the Internet of Things connects everything to the Internet, conducts data exchange, and transmits information via data-detecting devices including sensors, RFID, and global positioning systems. The Web of Things must be designed to detect, guide, and filter objects in order to provide clients with a variety of innovative data management services. The effects on transportation planning of autonomous cars, often known as self-driving, driverless, or robotic vehicles. Based on past vehicle technology experience, it examines the likelihood of such vehicles developing and being used quickly, their potential costs and benefits, how they will impact travel behaviour, and how they will influence planning choices like the best parking, roads, and public transportation options.